The Unintended Consequences of the Pandemic: The New Normal for College Students in South Korea and Taiwan - Chen, Wei-Lin; Song, Sue-Yeon; Yap, Ko-Hua (Frontiers in Public Health, 2021)
This study attempts to compare the impacts of the coronavirus (COVID-19) pandemic on college students’ lifestyles and mental health conditions in South Korea and Taiwan. As the COVID-19 outbreak has spread across the globe, it has brought significant changes to college campuses worldwide. College students have been heavily affected by the closure, as online learning has become increasingly common in higher education institutions. Using data collected from college students in South Korea and Taiwan in the spring of 2020, this study examines the effects of pandemic-related lifestyle changes on mental health conditions for college students in the two countries. The results were threefold. First, compared to college students in Taiwan, college students in South Korea reported greater decreases in time spent traveling, being with friends, eating at restaurants, and engaging in part-time employment, and greater increases in online shopping and ordering food for delivery. Second, college students in South Korea reported a higher level of worry, a greater possibility of contact with a person with COVID-19, and a lower level of happiness than did college students in Taiwan. Third, our findings indicate that social activities, including spending time with friends, were positively correlated with mental health conditions in South Korea and Taiwan. Comparing Korean and Taiwanese students’ lifestyle changes and mental health conditions amid the pandemic, the study argues that the decrease in socialization and interaction under these new circumstances may be a significant factor that explains an increase in mental health issues in Korean college students compared to Taiwanese students, given the increase in confirmed COVID-19 cases in South Korea and the corresponding greater use of online teaching platforms there than in Taiwan.